MEASURING EMPLOYEE SATISFACTION AS A TOOL FOR ENHANCING PRODUCTIVITY AND EMPLOYEE ENGAGEMENT - BOIKIVSKA, Halyna; VARENICHENKO, Alina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article investigates the assessment and management of employee job satisfaction as a key factor for enhancing organizational efficiency, productivity, and stability. It examines various approaches to defining job satisfaction, highlighting its multidimensional nature, which encompasses emotional, cognitive, and motivational components, as well as internal and external factors influencing employees’ perceptions and attitudes toward their work. Special attention is given to the methods of measuring job satisfaction, including standardized survey instruments such as the Job Descriptive Index (JDI) and the Job Satisfaction Survey (JSS), alongside quantitative indicators such as the employee Net Promoter Score (eNPS), staff turnover rate, and absenteeism levels. The study emphasizes the importance of combining these standardized approaches with flexible qualitative tools, including structured interviews, pulse surveys, and anonymous feedback boxes, to obtain a comprehensive, reliable, and practically meaningful assessment. It is demonstrated that the systematic application of these integrated methods allows organizations to objectively evaluate their current state, identify potential problem areas, enhance employee motivation and engagement, foster a positive corporate culture, and strengthen client loyalty. The findings confirm that an integrated and data-driven approach to managing job satisfaction serves as a strategic tool for improving organizational performance, supporting long-term growth, and ensuring sustainable development under modern socio-economic conditions. Moreover, effective implementation requires the alignment of quantitative and qualitative insights to support evidence-based managerial decisions, thereby increasing the resilience, adaptability, and overall competitiveness of enterprises in dynamic business environments.